2015
DOI: 10.1038/srep12800
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative activation-induced manganese-enhanced MRI reveals severity of Parkinson’s disease in mice

Abstract: We demonstrate that activation-induced manganese-enhanced magnetic resonance imaging with quantitative determination of the longitudinal relaxation time (qAIM-MRI) reveals the severity of Parkinson’s disease (PD) in mice. We first show that manganese ion-accumulation depends on neuronal activity. A highly active region was then observed by qAIM-MRI in the caudate-putamen in PD-model mice that was significantly correlated to the severity of PD, suggesting its involvement in the expression of PD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 51 publications
(85 reference statements)
1
35
0
Order By: Relevance
“…with MnCl 2 , and its neurons took up Mn 2+ when activated. A quantitative analysis indicated that Mn 2+ accumulates in neurons according to their activity, because Ca 2+ elevation is related to the firing activity in excitatory neurons [ 23 ]. In addition, its paramagnetic feature enables Mn 2+ to shorten the longitudinal relaxation time (T1) of water protons and thus enhance the T1-weighted MR signal that is specific to the tissues where Mn 2+ has accumulated [ 24 ], thus rendering it an excellent MRI-detectable contrast agent [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…with MnCl 2 , and its neurons took up Mn 2+ when activated. A quantitative analysis indicated that Mn 2+ accumulates in neurons according to their activity, because Ca 2+ elevation is related to the firing activity in excitatory neurons [ 23 ]. In addition, its paramagnetic feature enables Mn 2+ to shorten the longitudinal relaxation time (T1) of water protons and thus enhance the T1-weighted MR signal that is specific to the tissues where Mn 2+ has accumulated [ 24 ], thus rendering it an excellent MRI-detectable contrast agent [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative AIM-MRI uses a quantitative T1 value (or R1 value = T1 −1 ) to quantify the neuronal activity map of the entire brain, revealing the patterns and locations of changes in neuronal activity in animal models of PD. In particular, a quantitative analysis of the R1 value in the dorsal caudate-putamen determines the severity of PD and thus facilitates proper treatment (117). Unilateral SNc injury in the rat model of 6-hydroxydopamine (OHDA)-induced PD causes bilateral changes, and the T2 relaxation time of the bilateral SNc increases on MRI.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…The methods for Ca 2+ imaging were described previously (Osanai et al, 2006;Tamura et al, 2014;Kikuta et al, 2015). Briefly, postnatal day 12 (P12) to P17 GAD67-GFP mice of either sex were anesthetized with isoflurane (Mylan) and decapitated.…”
Section: Ca 2+ Imagingmentioning
confidence: 99%
“…As previously described (Kikuta et al, 2015), [Ca 2+ ] i elevation and manganese ion (Mn 2+ ) quenching was measured in striatal cells loaded with the ratiometric Ca 2+ sensitive dye Fura-2 LR/AM. The dye-loading methods used were as previously described (Osanai et al, 2006;Tamura et al, 2014).…”
Section: Ca 2+ Imagingmentioning
confidence: 99%
See 1 more Smart Citation